Effect of addition elemental Sulfur as additive in the selective reduction process of limonite nickel ore with the presents of sodium sulfate. Issue 1 (February 2021) - Pratama, Adiyaksa; Ananda, Rizky; Nurjaman, Fajar; Ferdian, Deni; Suharno, Bambang
Abstract: High temperatures in the smelting nickel ore increases the energy costs. The use of sulphur or sulphate as additives can optimize the reduction process at low temperatures through the formation of FeS compound. Biomass waste, which is palm shell charcoal, has potential as a reducing agent in the process of reducing laterite nickel ore because it has a fixed carbon value and a high heating value, besides that palm shell charcoal waste is more abundant as Indonesia's palm oil industry develops. This research was carried out to investigate the effect of addition elemental sulphur as additives and palm shell charcoal as reducing agent in the selective reduction process of limonite nickel ore. This research used limonite ore with 1.38% Ni and 38.2% Fe content. The reduction of nickel ore was conducted at a reduction in temperature variations (950°C, 1050°C, 1150°C) with the presents of 10 wt.% additive sodium sulfate (Na2 SO4 ) and addition 0%, 2.68% and 5% of elemental sulphur. The amount of reducing agent was stoichiometric variations (0.5, 1.0, 1.5). This research shows that the reduction process with 0% sulphur addition produced the most optimal grade and nickel recovery.